Self-consciousness - Rödl, Sebastian 1967- (Harvard Univ. Press, 2007)
The topic of this book is self-consciousness, which is a kind of knowledge, namely knowledge of oneself as oneself, or self-knowledge. Sebastian Rodl's thesis is that self-knowledge is not empirical; it does not spring from sensory affection. Rather, self-knowledge is knowledge from spontaneity; its object and its source are the subject's own activity, in the primary instance its acts of thinking, both theoretical and practical thinking, belief and action. The chapters of this book cover action and belief, freedom and reason, receptive knowledge and the second person. Each of these topics deserves its own book. And yet they would all be books on self-consciousness, for self-consciousness is the principle of their respective subject matters. Contemporary theories have been badly served by failing to acknowledge this. Taking the full measure of this insight requires a major conceptual reorientation in action theory, the philosophy of mind, and epistemology, which is begun in this book. As it can be said to be the principal thought animating Kant and his Idealist successors that self-consciousness occupies this central position, the book can be read as an attempt to recover and rejuvenate the achievement of the German Idealist tradition.